An Analysis of Brazil's Situation in the The Public Attitudes toward Clean Energy (PACE) Index in regard to Nuclear Energy - Fernando Barcellos Razuck (Brazilian Journal of Radiation Sciences)
Research on public perception of science and technology has become a relevant practice throughout the world, and public opinion and political support for nuclear technology are local and variable across countries. The Public Attitudes toward Clean Energy (PACE) Index is the world’s largest publicly released international study on what people think about nuclear energy. Surveying is conducted by Savanta, and commissioned and analysed by Radiant Energy Group, the PACE Index was set up to track support/opposition for clean energy sources, what drives those attitudes, and how institutions can better cater to what the public wants.  This paper aimed analysed the results of the PACE Index in order to evaluate the public's position in the world and in Brazil regarding the use of nuclear energy. Overall, it can be said that across the 20 countries surveyed, 46% of respondents support the use of nuclear energy and the preference for nuclear energy is larger than for onshore wind, biomass from trees, or gas with carbon capture and storage. Specifically, with regard to Brazil, it can be said that the public opposition to nuclear energy exceeds support, Reliability, Health & Safety and Climate Change are seen as an important energy attribute and the younger demographics are most supportive. In this sense, it is understood that through educational actions, scientific dissemination processes and discussions with society on the subject can help the process of public acceptance of nuclear energy.